2016
DOI: 10.1007/s10840-016-0153-2
|View full text |Cite
|
Sign up to set email alerts
|

Left sympathetic cardiac denervation in managing electrical storm: acute outcome and long term follow up

Abstract: LSCD is effective in controlling ES and continues to reduce the incidence of VAs during long term follow up. Pharmacological LSCD needs particular emphasis, as it can be performed at bedside, and can be a bail-out procedure in centres where sophisticated procedures like VATS-guided LSCD or radiofrequency ablation are not readily available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Echocardiography-guided percutaneous sympathectomy is a useful alternative for patients with hemodynamic instability. 33 In the present case, sympathectomy would definitely be considered as an option in case of ablation failure.…”
Section: Discussionmentioning
confidence: 86%
“…Echocardiography-guided percutaneous sympathectomy is a useful alternative for patients with hemodynamic instability. 33 In the present case, sympathectomy would definitely be considered as an option in case of ablation failure.…”
Section: Discussionmentioning
confidence: 86%
“…We included 14 nonrandomized studies in our final analysis. 5,[11][12][13][14][15][16][17][18][19][20][21][22][23] Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Prisma flow diagram for the study selection is shown in Figure 1. We included 14 nonrandomized studies in our final analysis 5,11‐23 . Majority of the studies were from North America.…”
Section: Resultsmentioning
confidence: 99%